PREVENTING CHILD MALTREATMENT: IS THERE A NEED FOR A EUROPEAN POLICY?. (7th October 2012) - Sethi, D; Mitis, F
Abstract : Background: The United Nations Secretary-General's report on violence against children has heightened awareness in countries of the victimisation of children worldwide. The response has been greater emphasis on child protection rather than primary prevention. Purpose: To raise the level of debate about the need for European wide policy on the primary prevention of child maltreatment. Methods: Policy analysis based on documents, survey of health ministry focal persons and age standardised mortality rates. Results: Child maltreatment is responsible for 1500 deaths in children under 5 years of age in the 53 countries of the WHO European Region. Deaths are the tip of the clinical iceberg and millions of children are affected annually. In spite the gravity of this problem, only 80% of European Member States have policies for child maltreatment, and only 40% focus on primary prevention. WHO is conducting surveys of adverse childhood experiences in Lithuania, Latvia, The former Yugoslav Republic of Macedonia, Albania, Montenegro, Romania. Results are being presented at national policy dialogues to prioritise prevention. Significance: Maltreatment constitutes one of the most severe forms of adverse experiences in childhood, and which are implicated in health risk behaviours and health effects such as the development of noncommunicable disease, mental illness and violence. Policy links are being made to the current global and European health agenda on noncommunicable disease, social determinants of health and Health 2020. This paper presents the evidence and discusses the need for a European policy to advocate for preventing child maltreatment.